Relativistic shock waves induced by ultra-high laser pressure. (24th February 2014) - Eliezer, Shalom; Nissim, Noaz; Raicher, Erez; Martínez-Val, José Maria
Abstract This paper analyzes the one dimensional shock wave created in a planar target by the ponderomotive force induced by very high laser irradiance. The laser-induced relativistic shock wave parameters, such as compression, pressure, shock wave and particle flow velocities, sound velocity and temperature are calculated here for the first time in the context of relativistic hydrodynamics. For solid targets and laser irradiance of about 2 × 1024 W/cm2, the shock wave velocity is larger than 50% of the speed of light, the shock wave compression is larger than 4 (usually of the order of 10) and the targets have a pressure of the order of 1015 atmospheres. The estimated temperature can be larger than 1 MeV in energy units and therefore very excited physics (like electron positron formation) is expected in the shocked area. Although the next generation of lasers might allow obtaining relativistic shock waves in the laboratory this possibility is suggested in this paper for the first time.